PERSEPSI DAN SIKAP MASYARAKAT TERHADAP AKTIVITAS PABRIK SMELTER DI DESA MOROSI KECAMATAN MOROSI KABUPATEN KONAWE - Sukmawati Abdullah; Yani Taufik; Rizal Sahyono (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2019)
This study aims to see community perceptions and attitudes towards the activities of smelter factories in Morosi Village, Morosi District, Konawe District. Perception in this research is the community's perspective on smelter factory activities. This study looks at perceptions and attitudes towards changes in income, employment opportunities, and business opportunities. The purpose of this study is to find out how the perceptions and attitudes of the community towards the impact of economic activities caused by smelter factories in Morosi Village, Morosi District, Konawe District. The population in this study is 97 heads of households. Determination of the sample is done by simple random sampling, so the sample in the study is 49 respondents. The results of this study indicate that people's perceptions and attitudes towards the impact of the existence of smelter factories on income, employment opportunities, and dominant business opportunities are in the neutral category. That is, the community considers that the activity of the smelter factory in Morosi Village does not have a significant influence on the economy of the local community.